(untitled) (Research, Society and Development, 2020)
Determine levels of digestible lysine for free-range chicken of the Caneludo Catolé, during the initial, growth and termination phases. Were used150 male and female poultry in confinement cages. The digestible lysine levels used per phase: initial (1-30 dias) 0.856, 0.978, 1.100, 1.223, 1.345%, growth (30-75 dias) 0.705, 0.806, 0.906, 1.007, 1.108% and termination (75-105 dias) 0.624, 0.713, 0.802, 0.891, 0.980%. Five treatments, three replicates, 10 chickens per experimental unit, distributed in a completely randomized design. Parameters of zootechnical evaluated: feed intake, weight gain, feed conversion ratio. The carcass characteristics evaluated: carcass, breast, drumstick, thigh, wing, neck, back, foot, gizzard, liver and heart yields. Meat quality evaluated: pH, shear force (kgf/g), cooking weight loss (%).The levels of digestible lysine influence in the initial phase with quadratic effect (P<0.01) in weight gain 1.225% and feed conversion ratio 1.175%. In the growth phase digestible lysine had a positive linear on feed intake (P<0.05) and weight gain (P<0.01) and linear decrease (P <0.01) for feed conversion ratio. In the termination phase, feed intake linearly increased (P<0.05), weight gain and feed conversion were quadratic (P<0.01), with levels calculated as 0.757 and 0.713%, respectively. Increasing linear responses were observed for carcass (%), breast (P<0.05) and drumstick (P<0.01) yields. The pH of the breasts showed a linear increasing effect (P<0.01), while shear force and cooking weight loss had a linear decreasing effect (P <0.01) with the increase of digestible lysine levels. The levels of digestible lysine recommended per phases: 1.175% initial, 1.108% growth and 0.713% termination.